The Role of Fintech in Bridging the Divide for Economic Empowerment - Miah Muhammed (Economics and Business, 2023)
The financial industry is experiencing transformation through the emergence of Financial Technology (Fintech) which brings forth fresh and innovative approaches to accessing and managing financial services. As digital financial services continue to disrupt traditional banking systems, they have the potential to significantly reduce disparity. This study explores the impacts of Fintech on promoting inclusion enabling access to capital and fostering economic empowerment. It sheds light on how Fintech advancements play a role in addressing economic gaps. Through a comprehensive review, this research highlights how Fintech innovations improve access for underserved populations. It examines both success stories and challenges faced in regions emphasising how adaptable Fintech solutions are within socioeconomic contexts, and ultimately underscores the power of Fintech as a catalyst for promoting inclusivity and empowerment in the economy. By providing insights into how Fintech divides, this study offers guidance for policymakers, financial institutions, entrepreneurs, and researchers who aim to leverage financial technology for fostering inclusivity and prosperity.